2017
DOI: 10.1007/s10620-017-4685-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Clinical Behavior in Crohn’s Disease: Factors Associated with Complicated Disease and Surgery

Abstract: Clinical behavior altered in about one-third of patients. The most frequent complication was a change to stricturing pattern. Disease location, current smoker, immunosuppressive therapy use, hospitalization, and abdominal surgery were factors associated with an unfavorable clinical evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…According to reports, the 5-year cumulative complication rate of CD patients was 48% -52%, and after 10 years was 69% -70%, about half of patients developed intestinal stenosis, 27,28 and the cumulative probability of CD patients without complications in 5, 10 and 20 years was 86.3, 66.4 and 52.2%, respectively. 29 The incidence of complications of IBD patients in this study was similar to that, and most patients combined with one severe complications, the cumulative incidence of patients with the course of >10 years was 48.35%, which was significantly higher than 36.99% of patients with the course of 0-10 years (P=0.044). The cumulative incidence of severe complications in patients with CD, UC, and IBDU also showed upward trends, but the difference of them between the disease course was not statistically significant (P>0.05), which may be due to insufficient follow-up time.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…According to reports, the 5-year cumulative complication rate of CD patients was 48% -52%, and after 10 years was 69% -70%, about half of patients developed intestinal stenosis, 27,28 and the cumulative probability of CD patients without complications in 5, 10 and 20 years was 86.3, 66.4 and 52.2%, respectively. 29 The incidence of complications of IBD patients in this study was similar to that, and most patients combined with one severe complications, the cumulative incidence of patients with the course of >10 years was 48.35%, which was significantly higher than 36.99% of patients with the course of 0-10 years (P=0.044). The cumulative incidence of severe complications in patients with CD, UC, and IBDU also showed upward trends, but the difference of them between the disease course was not statistically significant (P>0.05), which may be due to insufficient follow-up time.…”
Section: Discussionsupporting
confidence: 79%
“…and 57.8% patients, respectively, while in group A3 21.6% (P<0.001), 29 and the age of >50 years old is a risk factor for IBD infection. 30 In this study, the differences among the incidence of severe complications of UC patients at different onset age were statistically significant (P=0.005), the incidence of severe complications of patients with onset age ≥50 years old was significant higher than that of patients aged 20-49 years old (P<0.01), among which the incidence of severe malnutrition was significantly different (P<0.001).This may indicates that the onset age ≥50 years old may be an independent risk factor for severe complications of UC patients, UC patients with onset of disease in middle and old age are more prone to severe complications.…”
Section: Discussionmentioning
confidence: 87%
“…Why are SB lesions in patients with CD important in clinical practice? de Barros et al 10 . In another investigation using data obtained from the REACT trial involving 1,898 CD patients, SB lesions were more strongly associated with CD-related surgery than colonic lesions (odds ratio [OR], 2.03; 95% CI, 1.16-3.57).…”
Section: Importance Of Sb Lesions In Patients With CD For Clinical Prmentioning
confidence: 97%
“…Why are SB lesions in patients with CD important in clinical practice? de Barros et al [ 10 ] demonstrated the importance of the location of SB lesions according to the Montreal classification with a 65.2-month follow-up. An ileal (L1) lesion was more significantly associated with a complicated disease course (relative risk [RR], 1.64; 95% confidence interval [CI], 1.10–1.75) and stricturing behavior (RR, 2.11; 95% CI, 1.20–3.69) than a colonic (L2) lesion.…”
Section: Importance Of Sb Lesions In Patients With CD For Clinical Prmentioning
confidence: 99%
“…There were no studies to date including the frequency of use of most recently approved anti-TNF agents (e.g., golimumab and certolizumab pegol) or biologics with different mechanisms of action (e.g., vedolizumab or ustekinumab). Overall, studies mostly described cohorts of IBD patients, with four being performed exclusively in CD (17)(18)(19)(20) and two exclusively in UC patients (21,22) . TABLE 1 describes in detail the current status of the frequency of use of biologics in different countries from Latin America, in CD, UC or IBD overall.…”
Section: Resultsmentioning
confidence: 99%